Self-efficacy Siswa dalam Pembelajaran Matematika - Auliaul Fitrah Samsuddin; Heri Retnawati (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2022)
Self-efficacy is one of the affective factors that contributes to students’ learning. It is defined by the extent which one believes they can do to accomplish a task. Specifically in mathematics learning, self-efficacy is students’ belief of their mathematical ability. The current research investigated mathematics self-efficacy of middle school students in Makassar. 393 students were administered to 22 items mathematics self-efficacy questionnaire. It was found that students’ self-efficacy is in moderate category with all three dimensions (level, strength, generality) being in moderate category as well. Students in A and B-stratified school had slightly better self-efficacy than those who are in C-stratified school. Detailed on some questionnaire items is discussed as well.